El vocativo árabe / ya– como posible étimo de la interjección che / xe del castellano y el catalán valencianos: una apostilla a los diccionarios etimológicos - Pascual Asensi, Jorge (Revista de Filología Románica, 2008)
The interjection form che/xe represents one of the most appreciable characteristics of the Catalonian and Spanish speech in central region of Valencia. The final aim of this paper appears in correspondence with the absence of any etymological explanation of the term that, really, provides the linguistic origin of this one and the historical-geographic diffusion of its use. The result of the investigation leads to an etymological reformulation of the term hypothetically linked to the linguistic substrate of dialectal Andalusian Arabic and its late speakers, the Moorish, like determining of some linguistics peculiarities of the valencian area.